Inappropriateness of health care in Canada: a systematic review protocol - Squires, Janet E; Graham, Ian D; Grinspun, Doris; Lavis, John; Légaré, France; Bell, Robert; Bornstein, Stephen; Brien, Susan E; Dobrow, Mark; Greenough, Megan; Estabrooks, Carole A; Hillmer, Michael; et al. (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background There is increasing recognition in Canada and globally that a substantial proportion of health care delivered is inappropriate as evidenced by (1) harmful and/or ineffective practices being overused, (2) effective clinical practices being underused, and (3) other clinical practices being misused. Inappropriate health care leads to negative patient experiences, poor health outcomes, and inefficient use of scarce health care resources. The purpose of this study is to conduct a systematic review of inappropriate health care in Canada. Our specific objectives are to (1) systematically search and critically review published and grey literature for studies on inappropriate health care in Canada; (2) estimate the nature and magnitude of inappropriate health care in Canada and its provincial and territorial jurisdictions. Methods We will include all quantitative study designs reporting objective or subjective measurements of inappropriate health care in Canada over the last 10 years. We will search the following online databases: MEDLINE, Cochrane Central Register of Controlled Trials, EconLit, and ISI-Web of Knowledge, which contains Web of Science Core Collection-Citation Indexes, Science Citation Index Expanded, Conference Proceedings Citation Index-Science, and Conference Proceedings Citation Index-Social Science & Humanities. We will also search grey literature sources to identify provincial and national audits of inappropriate health care. Two authors will independently screen, assess data quality, and extract data for synthesis. Study findings will be synthesized narratively. We will organize our data into three care categorizations: preventive care, acute care, and chronic care. We will provide a compendium of inappropriate health care for each care category for Canada and each Canadian province and territory, where sufficient data exists, by calculating (1) overall medians of underuse, overuse, and misuse of clinical practices and (2) the range of medians of underuse, overuse, and misuse for each clinical practice investigated. Discussion This review will result in the first-ever evidence-based compendium of inappropriate health care in Canada. We will also develop detailed reports of inappropriate health care for each Canadian province and territory. Systematic review registration PROSPERO CRD42018093495